1995
DOI: 10.1182/blood.v86.4.1460.bloodjournal8641460
|View full text |Cite
|
Sign up to set email alerts
|

International Prognostic Index for aggressive non-Hodgkin's lymphoma is valid for all malignancy grades

Abstract: An International Prognostic Index (IPI) for patients with aggressive non-Hodgkin's lymphoma (NHL) has recently been published. The IPI is based on pretreatment clinical characteristics and developed on clinical trial patients, classified as intermediate grade according to the Working Formulation (WF). We applied this IPI in a population-based registry of NHL patients. This registry does not have the restrictions that usually hold for patients in clinical trials, eg, with respect to age and performance status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(51 citation statements)
references
References 5 publications
3
45
1
2
Order By: Relevance
“…The IPI risk and the severity of comorbidity were independent prognostic factors for patients with aggressive lymphoma. The prognostic impact of IPI risk has also been described in previous studies (Hermans et al, 1995;Maartense et al, 1998;Niitsu & Iijima, 2001;Sonnen et al, 2002;Wilder et al, 2002;Bai et al, 2003;Lee et al, 2003).…”
Section: Treatment Response and Survivalsupporting
confidence: 61%
See 1 more Smart Citation
“…The IPI risk and the severity of comorbidity were independent prognostic factors for patients with aggressive lymphoma. The prognostic impact of IPI risk has also been described in previous studies (Hermans et al, 1995;Maartense et al, 1998;Niitsu & Iijima, 2001;Sonnen et al, 2002;Wilder et al, 2002;Bai et al, 2003;Lee et al, 2003).…”
Section: Treatment Response and Survivalsupporting
confidence: 61%
“…Higher IPI risk and high impact comorbidity were both independent predictors of a lower complete response rate in our study. A lower complete response rate for patients with a higher IPI risk was also found in a population-based study in the western part of the Netherlands (Hermans et al, 1995). A considerable part of this variation could probably be explained by the higher proportion of dose reduction for patients with high IPI risk or high impact comorbidity.…”
Section: Treatment Response and Survivalsupporting
confidence: 52%
“…In contrast to reports that focal paratrabecular (PT) involvement is the most common involvement pattern in FL (Dick et al, 1974;McKenna et al, 1975;McKenna, 1992;Hermans et al, 1995), we found more commonly a combination of several patterns in our large series, similar to Torlakovic et al (2002). PT and nodular non-PT patterns were observed either alone or associated with one or several other patterns.…”
Section: Discussioncontrasting
confidence: 99%
“…Keywords: bone marrow pathology, follicular lymphoma, prognosis, statistical analysis. 1975, 1992Foucar et al, 1982) at diagnosis and has been considered by some, but not all authors as a poor prognostic factor (Romaguera et al, 1991;Hermans et al, 1995;Izumi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the International Index Project has been proposed as a model to define clinical risk in patients with diffuse large cell lymphoma (The International Non-Hodgkin's Lymphoma Prognostic Factors Project 1993) based on five prognostic features: age, performance status, extranodal involvement, stage and seric levels of LDH. Although this model has been shown to be useful in patients with nodal disease at presentation (Hermans et al 1995) it has not been tested in patients with primary extranodal presentation at diagnosis. Analysis of our data in patients with primary gastric lymphoma (PGL) does not confirm that the Index has prognostic significance.…”
Section: Introductionmentioning
confidence: 99%